Determining the Cost-Effective Methods for Heat Exchanger Maintenance Using Extreme Value Analysis (EVA) Ask ChatGPT - Anne Ting Ai Nee; Ainul Akmar Mokhtar; Noor Hazliza A Latip; Farah Nur Faizul; Nurul Hazwani Azmi (Platform, a Journal of Engineering, 2025)
This study discusses the application of extreme value analysis (EVA) to evaluate the remaining lifespan of four integral heat exchangers (HEX) at a chemical process plant. Data from plugged tubes and sample tube pit depth inspections, collected using the Internal Rotary Inspection System (IRIS), served as the primary input for the EVA model. The model was employed to establish corrosion rates based on 40% wall loss for the identified heat exchangers, which is pivotal in determining the minimum remaining wall thickness. The mean remaining helpful life was calculated using the best-fit life data analysis distribution, and the estimated number of tubes approaching 40% wall loss was also determined. This evaluation is critical for forecasting the functional lifespan of the heat exchangers and deciding whether tube plugging, retubing, or replacement is the most cost-effective option against operational risk during the upcoming planned shutdown or turnaround phase. Additionally, sensitivity analysis was conducted to simulate the viability of these options based on corrosion rates of 45% and 50% wall loss.